2011
DOI: 10.4061/2011/805187
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microbial Enzymes in the Bioremediation of Pollutants: A Review

Abstract: A large number of enzymes from bacteria, fungi, and plants have been reported to be involved in the biodegradation of toxic organic pollutants. Bioremediation is a cost effective and nature friendly biotechnology that is powered by microbial enzymes. The research activity in this area would contribute towards developing advanced bioprocess technology to reduce the toxicity of the pollutants and also to obtain novel useful substances. The information on the mechanisms of bioremediation-related enzymes such as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
245
0
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(261 citation statements)
references
References 53 publications
0
245
0
16
Order By: Relevance
“…Pretreatment of such wastewaters to bring about lipid hydrolysis makes them more amenable to conventional biological treatment and hydrolytic enzymes find promising applications in this sector. Such applications of lipases and other hydrolytic enzymes have been reviewed earlier Mrozik et al 2008;Karigar and Rao 2011).…”
Section: Bioremediation Of Oil and Grease (Oandg) Containing Wastewatermentioning
confidence: 99%
“…Pretreatment of such wastewaters to bring about lipid hydrolysis makes them more amenable to conventional biological treatment and hydrolytic enzymes find promising applications in this sector. Such applications of lipases and other hydrolytic enzymes have been reviewed earlier Mrozik et al 2008;Karigar and Rao 2011).…”
Section: Bioremediation Of Oil and Grease (Oandg) Containing Wastewatermentioning
confidence: 99%
“…A large number of enzymes from bacteria, fungi, and plants are involved in the biodegradation of toxic pollutants. On one hand systems biology approach has revealed that toxic heavy metals (like As, Cd) could be transferred and accumulated in animals and human beings via food chain, which would cause DNA damage and carcinogenic effects by their mutagenic ability (Seth et al 2007(Seth et al , 2008, while on the other hand its approach on bioremediation would contribute toward developing advanced bioprocess technology to reduce the toxicity of the pollutants and also to obtain novel useful biomaterials (Leung 2004;Karigar and Rao 2011).…”
Section: Systems Biology Approach To Bioremediationmentioning
confidence: 99%
“…Enzymes are proteins whose function is to catalyze chemical reactions in living systems (Karigar & Rao, 2011). They act on specific substrates, transforming them into products necessary for biological cycles, and participate in many edaphic processes such as organic residue decomposition, humic substance synthesis, nitrification, oxidation, xenobiotic degradation and nitrogen fixation, among others and organo-mineral complexes (Joinville et al, 2004).…”
Section: Introductionmentioning
confidence: 99%